COMPARATIVE ANALYSIS OF ENDOVASCULAR TREATMENT METHODS FOR CORONARY ARTERY CALCIFICATION DURING STENTING: INTRAOPERATIVE STUDY RESULTS - A.S. FEDOROV, A.N. SHISHKEVICH, V.N. KRAVCHUK, SH.M. ASADULAEV, O.YA. POREMBSKAYA, E.I. UMANTSEV, U.M. MURATBEKOVA (Паёми Сино)
Objective: To perform a comparative analysis of the intraoperative outcomes of endovascular treatment methods for coronary artery calcification (CAC).